Methanosarcina thermophila bioaugmentation and its synergy with biochar growth support particles versus polypropylene microplastics in thermophilic food waste anaerobic digestion. (September 2022) - Lee, Jonathan T.E.; Lim, Ee Yang; Zhang, Le; Tsui, To-Hung; Tian, Hailin; Yan, Miao; Lim, Shuhan; Abdul Majid, Maszenan bin; Jong, Mui-Choo; Zhang, Jingxin; Wang, Chi-Hwa; Ok, Yong Sik; et al.
Graphical abstract: Highlights: Methanosarcina thermophila was used as bioaugmentation, and tested against growth on biochar, biochar alone, growth on polypropylene microplastics, PP alone, and adding biochar separately. Biochar plus bioaugmentation improved methane yield of thermophilic food waste AD when started with a mesophilic inoculum. Double the concentration of bioaugmentation was tested using a thermophilic inoculum. An optimal ratio of biochar growth support to microbe concentration was discovered. All experimental conditions elicited an increase in BMP compared to the controls. Abstract: Both biochar supplementation as well as bioaugmentation have been shown in literature to improve the methane yield of anaerobic digestion. In this study, the combination of both are evaluated by growing Methanosarcina thermophila on biochar support particles prior to augmentation of thermophilic food waste anaerobic digestion. Biochar stand alone, bioaugmentation solely, a combination of both added separately or grown together, and utilizing polypropylene (PP) microplastics as growth support instead were all tested when starting up a thermophilic process from mesophilic inoculum. Methanosarcina thermophila and biochar supplementation displayed synergy, with 5% M. thermophila on 1 g/L biochar presenting a 32% increase in specific methane yield over the control. Double the bioaugmentation dosage/concentration was also trialled with a thermophilic inoculum, and 10% M. thermophila grown on 2 g/L biochar displayed the best results with a 20% increase specific methane yield from its control standard.